2009
DOI: 10.1128/aem.00616-09
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Soil by Copper Affects the Dynamics, Diversity, and Activity of Soil Bacterial Communities Involved in Wheat Decomposition and Carbon Storage

Abstract: A soil microcosm experiment was conducted to evaluate the influence of copper contamination on the dynamics and diversity of bacterial communities actively involved in wheat residue decomposition. In the presence of copper, a higher level of CO 2 release was observed, which did not arise from greater wheat decomposition but from a higher level of stimulation of soil organic matter mineralization (known as the priming effect). Such functional modifications may be related to significant modifications in the dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Priming effect is an increase in soil organic matter mineralization by microorganisms following fresh organic matter (FOM) input (Bingeman et al, 1953;Kuzyakov et al, 2000). After more than two decades of increasing research effort, PE-generating mechanisms, determinants and actors still need to be elucidated (Fontaine et al, 2003;Bernard et al, 2007Bernard et al, , 2009Bernard et al, , 2012Pascault et al, 2013;Chen et al, 2014). Based on a literature review, Fontaine et al (2003) proposed that PE can be generated by two different mechanisms: (1) indirectly via collateral damage exerted on soil organic matter (SOM) by extracellular enzymes released by FOM feeders, and (2) directly via the co-metabolism of energy-rich FOM catabolites by SOM feeders who mine SOM for nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Priming effect is an increase in soil organic matter mineralization by microorganisms following fresh organic matter (FOM) input (Bingeman et al, 1953;Kuzyakov et al, 2000). After more than two decades of increasing research effort, PE-generating mechanisms, determinants and actors still need to be elucidated (Fontaine et al, 2003;Bernard et al, 2007Bernard et al, , 2009Bernard et al, , 2012Pascault et al, 2013;Chen et al, 2014). Based on a literature review, Fontaine et al (2003) proposed that PE can be generated by two different mechanisms: (1) indirectly via collateral damage exerted on soil organic matter (SOM) by extracellular enzymes released by FOM feeders, and (2) directly via the co-metabolism of energy-rich FOM catabolites by SOM feeders who mine SOM for nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, using the energy-rich FOM, SOM feeders would increase the decomposition rate of the nutrient-rich SOM in a co-metabolism process, which would allow them to assimilate N and P. These authors concluded that any disturbances affecting the relative proportions of the two functional groups (FOM and SOM feeders) would impact the intensity of the PE. However, the identity of microorganisms that form part of the SOM-feeder group remains more or less unknown (Bernard et al, 2009;Kuzyakov, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This corroborates the findings of Benedict, Oladapo, and Emmanuel (1991), Adeniyi and Yusuf (2007) and Adefemi et al (2008), who reported that the level of heavy metal determined in the samples of Epe and Badagry Lagoon were lower than those reported in the sediment. The higher concentration of copper (4,7±0,03) in the water samples from Epe Lagoon than the standard specification (<1mg/L) by FEPA (2003) and WHO (1997) may be as a result of heavy microbial contamination of the water body (Numako & Nakai, 1995;Bernard et al, 2009). The findings showed higher value of dissolved oxygen in the water sample (9,0±0,02) than the standard specification (3,0-5,0mg/L; FEPA 2003).…”
Section: Discussionmentioning
confidence: 94%